Attitudes of the pioneers of Baghdadi cafés towards the songs of the fifties (Journal of the College of Basic Education, 2022)
It is noticeable in the songs of the present time that there are different types of them that are prepared and broadcast to the listener.Al-Baghdadi in particular (the capital) and with a very large amount of production, in a wide and prolific manner, and with the latestpossible technical technical methods, but only a few of them are memorized by the listeners for a period of time.A specific period of time, that is, the best song that does not live or be stored in the memory of the recipient except for several months. This is what we do not see.In the old Baghdadi songs (the fifties period). Whereas these songs are still preserved in the chests ofThe memory of the Baghdadi listener has become a popular heritage for his original community. It must also bear the characteristics ofEspecially so that every listener tends to it from the first moment until the present time. This trend is the justificationwhich deserves to be studied in this research in a scientifically correct manner, which may reflect a positive trend orI have a negative attitude towards these songs so that it is possible to benefit from it as an effective contribution to the development and development of taste.Baghdadi community.